Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Pada Materi Satuan Berat Siswa Kelas II SDN Kalicari 01 Semarang - Auliya Fatkhiyah; Noor Miyono; Ikha Listyarini; Tutik Wahyuni (Alifbata : Jurnal Pendidikan Dasar, 2023)
The purpose of this study was to improve the learning outcomes of weight unit material using problem-based learning model for grade II students. This research was conducted at SDN Kalicari 01 Semarang involving 26 grade II students. The research method used was classroom action research method using 2 cycles. Data collection techniques used observation, interviews, and tests. The data obtained were then analyzed using quantitative and qualitative methods. The results of this study indicate that student learning outcomes improve in each cycle. In cycle I students who reached the KKM were only 69.23% (18 students). In cycle II students who reached the KKM increased to 24 students a percentage of 92.30%. Based on the results of the study, it can be concluded that learning outcomes on the material of units of weight of objects in grade 2 students can be improved through the use of Problem Based Learning learning model.